AP-1 Repressor Protein JDP-2: Inhibition of UV-Mediated Apoptosis through p53 Down-Regulation - Piu, Fabrice (American Society for Microbiology, 2001)
Members of the AP-1 transcription factor family, especially c-Jun and c-Fos, have long been known to mediate critical steps in the cellular response to ultraviolet (UV) irradiation. We sought to examine whether two newly discovered members of the AP-1 family, JDP-1 and JDP-2, also participate in the mammalian UV response. Here we report that JDP-2, but not JDP-1, is transiently induced upon UV challenge and that elevated levels of JDP-2 increase cell survival following UV exposure. This protective function of JDP-2 appears to be mediated through repression of p53 expression at the transcriptional level, via a conserved atypical AP-1 site in the p53 promoter.